Islamic Faith and Philosophy in Durant’s Encyclopedia "The Story of Civilization" - Critical Analytical Study - - Malahmeh, Amer Salameh Falah (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: This research deals with collecting and studying what Durant wrote about the origins of the Islamic faith, such as monotheism, fate, destiny, and prophecies, as well as philosophy, Sufism, and Islamic morals, in chapter 13 of “The Age of Faith for Civilization” in his encyclopedia "The Story of Civilization". The researcher traced what Durant wrote, about the Islamic faith and aimed to explain the mistakes that Durant faced when talking about Islamic faith issues, Islamic philosophy, and Sufism and discussing them. Methods: The study used the analytical approach by analyzing Durant’s texts regarding Islamic doctrine, Islamic philosophy and Sufism, as well as the critical approach of the similarities raised by Durant about it and showing their weaknesses. Results: The study showed the appearance of Jewish influence in Durant’s writings on the story of civilization, and the invalidity of what he said about the doctrines of Islam, as well as his statement that algebra is the doctrine of the Qur’an and the Sunnah, as well as the invalidity of his questioning the call of the Prophet - Muhammad (peace and blessings of Allaah be upon him) - and challenged him with most Muslim philosophers. Conclusions: Studying the Encyclopedia of the history of civilization in most cognitive aspects, especially the legal ones, and revealing the errors and similarities contained in it.